CHALLENGES IN IMPLEMENTING GOOD CORPORATE GOVERNANCE AMONG FIRMS IN THE BATAM FREE TRADE ZONE: A LITERATURE REVIEW - Robin (PT. Radja Intercontinental Publishing, 2024)
The Batam Free Trade Zone and Free Port (KPBPB) is one of Indonesia’s most important investment nodes, yet growth in investment value is not necessarily accompanied by improvements in governance quality at the firm level. This study aims to map and synthesise the challenges of implementing good corporate governance (GCG) among firms operating in the zone. A systematic literature review was conducted following the PRISMA 2020 reporting protocol, covering Scopus-, SINTA-, Garuda-, and DOAJ-indexed articles published between 2020 and 2025. Articles were screened using predefined inclusion and exclusion criteria and analysed through thematic content analysis. The synthesis identifies four interrelated layers of challenges: (1) institutional-regulatory challenges arising from dual authority in zone management and the shifting licensing regime; (2) ownership-structure challenges stemming from the dominance of foreign-investment subsidiaries and family firms, which weaken independent oversight; (3) transparency and disclosure challenges among non-listed firms that fall outside the reach of capital-market regulation; and (4) internal-capacity and sustainability challenges driven by global supply-chain pressures. The study proposes a four-layer conceptual framework and five empirically testable propositions, and argues that conventional GCG mechanisms developed in the context of listed firms are insufficient to explain governance practices within free trade zones.